Inclusiveness in the Panchayati Raj Institutions. Issue 1 (June 2019) - Sukumar, N.; Lal, L. David; Mishra, Vinod Kumar
Abstract: The 73rd amendment of the Indian Constitution has evolved as a significant mechanism for devolution of power and democratic decentralisation. The template was to transform the power relation at three levels, that is, family, community and state apparatuses. Studies on the representation of underprivileged groups (caste, gender and tribes) in the panchayati raj institutions (PRIs) have highlighted the continued discrimination against these groups. This article analyses both enabling and disabling factors which affect the performance of the elected representatives (ERs) belonging to the scheduled castes, scheduled tribes and women from seven states. The findings (both qualitative and quantitative) of the study highlight general as well as group-specific enabling and disabling factors that impact the performance of the ERs in PRIs.